MAKNA PERSETUJUAN BERSAMA DPR DAN PRESIDEN DALAM PEMBENTUKAN UNDANG-UNDANG - Aris Arianto; Afif Hasbullah; Sholihan Sholihan (MIMBAR YUSTITIA, 2019)
The establishment of the Act must be approved by the President as stated in Article 20 of the 1945 Constitution paragraph (2). Interesting when Indonesia uses a presidential system with the separation of powers. However, in the formation of the Act involving the President. Article 20 paragraph (2) of the 1945 Constitution confirms the necessity of mutual agreement in the discussion and ratification of the Law. However, there are other assertions, namely that in Article 20 paragraph (5) of the 1945 Constitution, even without the President's signature, the Act can still be promulgated within 30 days of the Draft Law being discussed. Things like that can't just happen without a reason. Therefore, the writing of this study will look for the meaning of the agreement between the DPR and the President in the formation of the Law and how the legal politics of Article 20 paragraph (5) of the 1945 Constitution. The writing of this study is focused on researching and searching for the meaning of mutual agreement and focusing on legal politics from Article 20 paragraph 5 of the 1945 Constitution. The research method in this writing is normative juridical. The results of the research can be concluded that the meaning of the joint agreement between the DPR and the President in the establishment of the Law is an agreement in determining the policy in the form of a Law which is a reflection of the principle of checks and balances. Legal politics Article 20 paragraph (5) of the 1945 Constitution is an affirmation of Article 20 paragraph (2) of the 1945 Constitution or can be called an affirmation of collective agreement. The establishment of the Act must be approved by the President as stated in Article 20 of the 1945 Constitution paragraph (2). Interesting when Indonesia uses a presidential system with the separation of powers. However, in the formation of the Act involving the President. Article 20 paragraph (2) of the 1945 Constitution confirms the necessity of mutual agreement in the discussion and ratification of the Law. However, there are other assertions, namely that in Article 20 paragraph (5) of the 1945 Constitution, even without the President's signature, the Act can still be promulgated within 30 days of the Draft Law being discussed. Things like that can't just happen without a reason. Therefore, the writing of this study will look for the meaning of the agreement between the DPR and the President in the formation of the Law and how the legal politics of Article 20 paragraph (5) of the 1945 Constitution. The writing of this study is focused on researching and searching for the meaning of mutual agreement and focusing on legal politics from Article 20 paragraph 5 of the 1945 Constitution. The research method in this writing is normative juridical. The results of the research can be concluded that the meaning of the joint agreement between the DPR and the President in the establishment of the Law is an agreement in determining the policy in the form of a Law which is a reflection of the principle of checks and balances. Legal politics Article 20 paragraph (5) of the 1945 Constitution is an affirmation of Article 20 paragraph (2) of the 1945 Constitution or can be called an affirmation of collective agreement.